Stalled : the representation of women in Canadian governments - Arscott, Jane; Tremblay, Manon, 1964-; Trimble, Linda, 1959- (UBC Press, 2013)
This book provides a detailed roadmap of women's political representation as candidates, office-holders, cabinet ministers, party leaders, and as representatives of the Crown at all levels of government across Canada. it also explores the efforts of political parties, governments, and women's organizations to recruit more women candidates and to promote women into executive positions. As well, it assesses prospects for gender parity in political office in each jurisdiction and institution.
Keywords: Women -- Political activity -- Canada.; Women legislators -- Canada.; Femmes parlementaires -- Canada.; Femmes en politique -- Canada.; Femmes -- Activité politique -- Canada.; SOCIAL SCIENCE -- Women's Studies.; Women legislators; Women -- Political activity; Canada; Regierung; Politikerin; Kanada